Advanced digital signal processing for flexible optical access networks - Ferreira, Ricardo Manuel da Silva (2018)
Demand by bandwidth in the optical access networks (OANs) are increasing signiﬁcantly, since services from the mobile backhaul to the ﬁxed Internet end-user require increasingly higher performance and ﬂexibility. This demand has motivated the research community to propose new optical transmission solutions for the next-generation passive optical networks (PONs) towards to improve the spectral eﬃciency through an increase in the number of users, ﬂexible data rates, higher extended reach and heterogeneous services, fulﬁlling at the same time network equipment cost constraints. Coherent ultra-dense wavelength division multiplexing (UDWDM) PON appears as one of the solutions for next-generation OANs, combining coherent detection, advanced modulation formats and digital signal processing (DSP). This technology beneﬁts the network with a virtual point-to-point (P2P) conﬁguration, i.e. with dedicated UDWDM channels per end-user, supporting a longer signal reach and a larger number of users due to the improved sensitivity and selectivity provided by coherent detection. However, coherent PON with advanced modulation formats requires eﬃcient DSP, with ﬂexible working conditions towards diﬀerent type of services, diﬀerent data rates or modulation formats, which entails cost issues for its access commercialization. The main goal of the present work is to propose DSP hardware architectures for coherent UDWDM-PON technology, exploiting eﬃcient and low complexity solutions. Therefore, the practical realization is addressed to develop digital PON transceivers based on advanced DSP for both optical line terminal (OLT) and optical network unit (ONU), combining experimental and ﬁeld-trial validations with high capacity systems and real-time processing.